Population, climate change, and global justice: A moral framework for debate - Elizabeth Cripps (The Journal of Population and Sustainability, 2017)
This paper outlines a moral framework for the debate on global population policy. Questions of population, climate justice and global justice are morally inseparable and failure to address them as such has dangerous implications. Considerations of population lend additional urgency to existing collective duties to act on global poverty and climate change. Choice-providing procreative policies are a key part of that. However, even were we collectively to fulfil these duties, we would face morally hard choices over whether to introduce incentive-changing procreative policies. Thus, there is now no possible collective course of action which is not morally problematic.